2014
DOI: 10.1111/risa.12178
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Factors for Wastewater‐Irrigated Asian Vegetables and a Probabilistic Rotavirus Disease Burden Model for Their Consumption

Abstract: Many farmers in water-scarce regions of developing countries use wastewater to irrigate vegetables and other agricultural crops, a practice that may expand with climate change. There is a number of health risks associated with wastewater irrigation for human food crops, particularly with surface irrigation techniques common in the developing world. The World Health Organization recommends using quantitative microbial risk assessment (QMRA) to determine if the irrigation scheme meets health standards. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…However, other studies reported that the use of wastewater from Nhue River was significantly associated with helminth and intestinal protozoa infections as well as self-reported diarrhoea (Pham-Duc et al, 2013. In order to better understand the risk of the specific causative agents, a context-specific QMRA is required (Mok and Hamilton, 2014). For example, as shown by Pham-Duc (2012), the estimated risk of diarrhoeal diseases due to the exposure to wastewater reused for rural agriculture across communities in Hanam was 100-fold greater than the acceptable risks (Pham-Duc, 2012).…”
Section: Potential Implication For Public Healthmentioning
confidence: 97%
“…However, other studies reported that the use of wastewater from Nhue River was significantly associated with helminth and intestinal protozoa infections as well as self-reported diarrhoea (Pham-Duc et al, 2013. In order to better understand the risk of the specific causative agents, a context-specific QMRA is required (Mok and Hamilton, 2014). For example, as shown by Pham-Duc (2012), the estimated risk of diarrhoeal diseases due to the exposure to wastewater reused for rural agriculture across communities in Hanam was 100-fold greater than the acceptable risks (Pham-Duc, 2012).…”
Section: Potential Implication For Public Healthmentioning
confidence: 97%
“…For example, a rotavirus infection estimation from consuming crops that have been irrigated with effluents from stabilization ponds was 10 −3 and 10 −4 [45], and the median annual probability of infection from the consumption of vegetables that have been irrigated with wastewater using an overhead sprinkler also ranged from 10 −3 to 10 −4 per year [46]. The daily probability of illness from eating raw unwashed vegetables irrigated with untreated wastewater the Bogotá river receives from the city and towns ranged between 0.62 and 0.85 [47].…”
Section: Discussionmentioning
confidence: 99%
“…Hamilton and Mok [156] conducted an experiment to determine the volume of water collected in Asian vegetables and lettuce after irrigation by sprinkling with wastewater. The proposed objective contributed to the decrease in the knowledge gap, associated with the estimation of rotavirus microbiological risk in high consumption products in China.…”
Section: Assessment Of the Risk Associated With The Use Of Wastewatermentioning
confidence: 99%